Solitary fibrous tumor of the pancreas clinically mimicking a pancreatic neuroendocrine tumor: Cytologic pitfalls when a transgastric approach is utilized. Issue 11 (14th August 2021) - Marotti, Jonathan D.; Liu, Xiaoying; Jamot, Sehrish; Gardner, Timothy B.; Gordon, Stuart R.; Kerr, Darcy A.
Abstract: Solitary fibrous tumor (SFT) involving the pancreas is a rare entity often diagnosed on surgical specimens rather than cytology samples. Pancreatic SFT frequently mimics pancreatic neuroendocrine tumor radiographically, which presents unique challenges to the cytologist during rapid on‐site assessment. We describe a case of pancreatic SFT with a focus on the cytologic pitfalls that might be encountered during transgastric procedures. We also review the available cytologic findings of prior pancreatic SFT cases.